Highly uniform and vertically aligned SnO2 nanochannel arrays for photovoltaic applications - Kim, Jae-Yup; Kang, Jin Soo; Shin, Junyoung; Kim, Jin; Han, Seung-Joo; Park, Jongwoo; Min, Yo-Sep; Ko, Min Jae; Sung, Yung-Eun (ROYAL SOC CHEMISTRY, 2015)
Nanostructured electrodes with vertical alignment have been considered ideal structures for electron transport and interfacial contact with redox electrolytes in photovoltaic devices. Here, we report large-scale vertically aligned SnO2 nanochannel arrays with uniform structures, without lateral cracks fabricated by a modified anodic oxidation process. In the modified process, ultrasonication is utilized to avoid formation of partial compact layers and lateral cracks in the SnO2 nanochannel arrays. Building on this breakthrough, we first demonstrate the photovoltaic application of these vertically aligned SnO2 nanochannel arrays. These vertically aligned arrays were directly and successfully applied in quasi-solid state dye-sensitized solar cells (DSSCs) as photoanodes, yielding reasonable conversion efficiency under back-side illumination. In addition, a significantly short process time (330 s) for achieving the optimal thickness (7.0 mu m) and direct utilization of the anodized electrodes enable a simple, rapid and low-cost fabrication process. Furthermore, a TiO2 shell layer was coated on the SnO2 nanochannel arrays by the atomic layer deposition (ALD) process for enhancement of dye-loading and prolonging the electron lifetime in the DSSC. Owing to the presence of the ALD TiO2 layer, the short-circuit photocurrent density (J(sc)) and conversion efficiency were increased by 20% and 19%, respectively, compared to those of the DSSC without the ALD TiO2 layer. This study provides valuable insight into the development of efficient SnO2-based photoanodes for photovoltaic application by a simple and rapid fabrication process.
Keywords: SENSITIZED SOLAR-CELLS; TIO2 NANOTUBE ARRAYS; ATOMIC LAYER DEPOSITION; ULTRAHIGH ASPECT RATIO; SHRINKING CORE MODEL; TIN OXIDE; ELECTROCHEMICAL ANODIZATION; CONVERSION EFFICIENCY; NANOPOROUS ELECTRODE; NANOCRYSTALLINE TIO2